New Methods of Assessing Damage from Environmental Pollution - GRACHEV, Vladimir; NOVOSELOV, Andrey; NOVOSELOVA, Irina; PLIAMINA, Olga (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018DO - 10.14505//jemt.v9.1(25).13, 2018)
The process of developing methods for the economic assessment of environmental damage is subject to the requirements of world society, the policies of leading countries. The authors disclosed the existing approaches to the economic assessment of damage and showed the need for their development. The need for ecological rehabilitation of territories contaminated in past periods led to the creation and practical use of methods for the economic evaluation of past damage. The authors proposed a new approach to the economic assessment of past damage, which takes into account economic and assimilation factors. In addition, the article proposes a method for the economic evaluation of damage from emergencies, taking into account the cascading effects of the damage caused to the environment, the economy, the society and natural resources. The proposed method allows considering the indirect damages transmitted in the selected directions of the assessment taking into account the time factor.